(untitled) (Economia Aplicada, 2007)
This study investigates the relationship between socioeconomic factors and mental depression emphasizing the educational effect. Analyses for men and women were performed separately, using a 2003 Brazilian Household Survey (PNAD). It was verified that socioeconomic conditions can interfere in the probability of both men and women to develop depressive symptoms. However, the effect of these conditions is larger for women. Finally we concluded that higher education can reduce the risk of depression.